The Globin Gene Family in Arthropods: Evolution and Functional Diversity - Prothmann, Andreas; Hoffmann, Federico G.; Opazo, Juan C.; Herbener, Peter; Storz, Jay F.; Burmester, Thorsten; Hankeln, Thomas (Frontiers in Genetics, 2020)
Globins are small heme-proteins that reversibly bind oxygen. Their most prominent roles in vertebrates are the transport and storage of O2 for oxidative energy metabolism, but recent research has suggested alternative, non-respiratory globin functions. In the species-rich and ecologically highly diverse taxon of arthropods, the copper-containing hemocyanin is considered the main respiratory protein. However, recent studies have suggested the presence of globin genes and their proteins in arthropod taxa, including model species like Drosophila. To systematically assess the taxonomic distribution, evolution and diversity of globins in arthropods, we systematically searched transcriptome and genome sequence data and found a conserved, widespread occurrence of three globin classes in arthropods: hemoglobin-like (HbL), globin X (GbX) and globin X-like (GbXL) protein lineages. These globin types were previously identified in protostome and deuterostome animals including vertebrates, suggesting their early ancestry in Metazoa. The HbL genes show multiple, lineage-specific gene duplications in all major arthropod clades. Some HbL genes (e.g., Glob2 and 3 of Drosophila) display particularly fast substitution rates, possibly indicating the evolution of novel functions, e.g., in spermatogenesis. In contrast, arthropod GbX and GbXL globin genes show high evolutionary stability: GbXL is represented by a single-copy gene in all arthropod groups except Brachycera, and representatives of the GbX clade are present in all examined taxa except holometabolan insects. GbX and GbXL both show a brain-specific expression. Most arthropod GbX and GbXL proteins, but also some HbL variants, include sequence motifs indicative of potential N-terminal acylation (i.e. N-myristoylation, 3C-palmitoylation). All arthropods except for the brachyceran Diptera harbor at least one such potentially acylated globin copy, confirming the hypothesis of an essential, conserved globin function associated with the cell membrane. In contrast to other animals, the fourth ancient globin lineage, represented by neuroglobin, appears to be absent in arthropods, and the putative arthropod orthologues of the fifth metazoan globin lineage, androglobin, lack a recognizable globin domain. Thus, the remarkable evolutionary stability of some globin variants is contrasted by occasional dynamic gene multiplication or even loss of otherwise strongly conserved globin lineages in arthropod phylogeny.